A Tetraethynyl[5]cumulene - Marshall, Jonathan L.; Arslan, Funda; Januszewski, Johanna; Ferguson, Michael J.; Tykwinski, Rik R. (Helvetica Chimica Acta, 2019)
The first example of a new class of carbon-rich molecules is introduced, namely, a derivative of tetraethynyl[5]cumulene (TE5C). The use of sterically demanding pendent groups is the decisive structural feature to provide a stable product. Whereas triisopropylsilyl groups are seemingly not sufficiently large to afford an isolable cumulene product, switching to the larger tris(3,5-di-tert-butylphenyl)methyl (supertrityl') groups gives a crystalline, stable compound ([5]TE). The structural and electronic properties of [5]TE are examined in comparison to its closest known molecular relatives, tetraaryl[5]cumulenes.
CRIS-Team WoS Importer:2019-04-09

Spatially and temporally resolved monitoring of doping polybenzimidazole membranes with phosphoric acid - Arslan, Funda; Böhm, Thomas; Kerres, Jochen; Thiele, Simon (Journal of Membrane Science, 2021)
Polybenzimidazole-based membranes in high temperature proton exchange membrane fuel cells require doping with phosphoric acid to enable proton conductivity. The level of phosphoric acid doping is traditionally determined by titration or weighing, but these methods only provide limited information, since they do not offer spatial resolution. We show that confocal Raman microscopy can not only provide information on the level of doping, but in addition about the spatial distribution of the dopant. We prove that doping is a diffusion-limited process, leading to a spatially inhomogeneous distribution of phosphoric acid unless doping is performed to saturation. Further, evidence of a slow redistribution of the dopant within a freestanding membrane under ambient conditions is provided. Confocal Raman microscopy can be used as a non-invasive measurement tool to investigate status and progress of doping a membrane with phosphoric acid.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Acid doping level (ADL); Acid uptake (AU); Fuel cells (FCs); High temperature (HT); Phosphoric acid (PA); Polybenzimidazole (PBI); Polymer electrolyte membrane; Raman spectroscopy

The influence of intrinsically proton conductive electrode binder materials on HT-PEMFC performance - Arslan, Funda; Dirsch, Jens; Wagner, Maximilian; Freiberg, Anna; Komma, Miriam; Kerres, Jochen; Thiele, Simon; Böhm, Thomas (Journal of Power Sources, 2023)
High temperature proton exchange membrane fuel cells (HT-PEMFCs) typically employ either acid-absorbing or hydrophobic electrode binders in their catalyst layers (CLs). A recently introduced alternative is the ionomeric binder PWN, poly(2,3,5,6-tetrafluorostyrene-4-phosphonic acid). In literature, PWN with a phosphonation degree of 70% was shown to remarkably improve HT-PEMFC performance. Here, we investigate the influence of the phosphonation degree (40–95%) of this ionomeric binder on HT-PEMFC performance. PWN is employed in the cathode CL and compared to the commonly used polytetrafluoroethylene (PTFE) binder. The electrochemical behavior is tested at 180 °C at ambient pressure under H2/air conditions using a commercial phosphoric acid (PA)-doped PBI-membrane. HT-PEMFCs with PWN generally outperform fuel cells (FCs) with PTFE after a full break-in regarding peak power density (PPD), activation overpotential (as studied by Tafel analysis), and reproducibility in the mass transport region. Further, PWN-electrodes show higher electrochemically active surface areas (ECSAs) than PTFE-electrodes after completing the break-in. We find that the phosphonation degree has a substantial impact on the PPD, with PWNs with lower phosphonation degrees (40–60%) outperforming highly phosphonated PWNs (70–95%). Taken together, PWN as an ionomeric electrode binder in HT-PEMFCs shows remarkable improvements in performance, but a precise adjustment of the phosphonation degree is required to obtain optimal results.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Binder; Fuel cell; High temperature; Ionomer; Phosphoric acid; Proton exchange membrane; PWN